Skin lesions associated with invasive devices in highly complex neonatal and pediatric patients - Ribeiro, Wanderson Alves; Oliveira, Ane Raquel de; Constantino, Gabriel Nivaldo Brito; Santos, Larissa Christiny Amorim dos; Guedes, Miriam Maria Ferreira; Souza, Érica Motta Moreira de; Reis, Elcio Gomes dos (Brazilian Journal of Science, 2024)
The skin is the largest organ of the human body. It has three layers: epidermis, dermis and hypodermis. The epidermis performs multiple functions in the body, standing out as a defensive barrier and internal integrity in addition to containing the evasion of moisture, and exogenous substances. Injury is by definition any interruption in the continuity of the skin regardless of its extent and may be chronic or acute. A newborn’s skin is delicate and vulnerable, and the use of invasive devices in highly complex care can negatively affect its integrity. This review study addressed data from Brazilian research on newborn skin in intensive hospital treatment units. The studies evaluated were obtained from the SciELO, Medline and Lilacs, Google Scholar and Elsevier databases. The inclusion criteria were articles, monographs, dissertations and theses published in the period between 2018 and 2023, in Portuguese with a pre-established theme, and the exclusion criteria were articles, monographs, dissertations and repeated theses, incomplete manuscripts and with unauthorized access free of charge. As results, 3 categories were obtained: Category 1 – Main causes of skin lesions in newborns and highly complex children. Category 2- Prevention measures in newborns and highly complex children with skin lesions. Category 3- Highly complex skin care strategies for newborns and children. It is evident that due to the high susceptibility of newborns and children to develop highly complex skin lesions, it requires greater attention from the nursing team. Early detection of the risk of skin lesions and the use of prophylaxis enable a better quality of life for newborns hospitalized in high complexity, avoiding and minimizing skin lesions caused by the care provided.